DAMPAK PERGAULAN BEBAS KALANGAN REMAJA DALAM PERSPEKTIF HUKUM DAN KRIMINOLOGI - Fauzan azima; Maudy anjani; Tomi J.E hutasoit; Herli antoni (JOURNAL SAINS STUDENT RESEARCH, 2024)
Promiscuity is a form of deviant behavior where "free" means crossing the boundaries of existing norms. We often hear about the problem of promiscuity both in the environment and in the mass media. Teenagers are individuals or groups whose emotions are very vulnerable, minimal knowledge and the invitation of friends who socialize freely means that the potential of the younger generation in the advancement of the times is increasingly reduced. Free association is one of the life needs of social creatures who in their daily lives need other people and relationships between humans through social interactions. Association is every individual's human right and it must be liberated, so that every human being should not be restricted in social relations, let alone discrimination, because this violates human rights. So, human interaction should be free in positive terms, and still comply with legal norms, religious norms, culture and social norms, so if medically speaking, if the association is free but not regular or not limited by the rules and norms of human life, of course it will not cause access to free association like today. Teenagers are the next generation who will build the nation in a better direction who have far-sighted thinking and activities that can benefit themselves, their families and the surrounding environment. Therefore, society, especially teenagers, must receive special attention, both from themselves, their parents and the surrounding community.